2011
DOI: 10.1172/jci58050
|View full text |Cite
|
Sign up to set email alerts
|

Genes regulating lymphangiogenesis control venous valve formation and maintenance in mice

Abstract: Chronic venous disease and venous hypertension are common consequences of valve insufficiency, yet the molecular mechanisms regulating the formation and maintenance of venous valves have not been studied. Here, we provide what we believe to be the first description of venous valve morphogenesis and identify signaling pathways required for the process. The initial stages of valve development were found to involve induction of ephrin-B2, a key marker of arterial identity, by venous endothelial cells. Intriguingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
304
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(332 citation statements)
references
References 34 publications
21
304
1
Order By: Relevance
“…Gene-targeted mice expressing a Cre-recombinase or a fluorophore under an LEC-specific promoter have recently been generated, [32][33][34][35][36] but only 2 IVM studies performed in such mice have been reported so far. 35,36 Therefore, to date, LVs have mainly been visualized in IVM by in vivo labeling with intracutaneously injected fluorescent antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Gene-targeted mice expressing a Cre-recombinase or a fluorophore under an LEC-specific promoter have recently been generated, [32][33][34][35][36] but only 2 IVM studies performed in such mice have been reported so far. 35,36 Therefore, to date, LVs have mainly been visualized in IVM by in vivo labeling with intracutaneously injected fluorescent antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Specific pathogen-free C57BL/6J mice, Tie2-GFP (FVB/N) mice, and R26 mTmG/+ mice were purchased from the Jackson Laboratory. Prox1-GFP mice (17), Vegfc +/LacZ mice (34), and Prox1-Cre ERT2 mice (58) were transferred and bred in our pathogen-free animal facilities. Prox1-GFP mice were backcrossed for 6 or more generations to C57BL/6J.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, the initiation of lymphatic valve formation in the mouse embryo correlates with the onset of lymph flow (Sabine et al, 2012). Recent work revealed that ECs located directly adjacent to venous and lymphatic valves display distinct morphological characteristics; ECs immediately upstream of the valve are elongated, whereas rounded ECs predominate downstream of the valve (Bazigou et al, 2011). To date, the molecular players responsible for transducing the mechanosensory signals that initiate valve development remain elusive.…”
Section: Lymphatic Valve Formationmentioning
confidence: 99%
“…Although beyond the scope of this review, it is important to point out that the morphogenetic process of valve development occurs similarly in the venous vasculature; genes important for lymphatic valve morphogenesis also play key roles in venous valve formation (Bazigou et al, 2011;Munger et al, 2013). Furthermore, Srinivasan and Oliver have recently demonstrated that Prox1 dosage is crucial for the formation of embryonic lymphovenous valves, which separate the developing lymphatic vasculature from the jugular and subclavian veins (Srinivasan and Oliver, 2011).…”
Section: Lymphatic Valve Formationmentioning
confidence: 99%